A High‐Valent Iron(IV) Peroxo Core Derived from O2. Issue 2 (28th October 2015) - Kishima, Takahiro; Matsumoto, Takahiro; Nakai, Hidetaka; Hayami, Shinya; Ohta, Takehiro; Ogo, Seiji
Abstract: Dioxygen‐tolerant [NiFe] hydrogenases catalyze not only the conversion of H2 into 2 H + and 2 e − but also the reduction of O2 to H2 O. Chemists have sought to mimic such bifunctional catalysts with structurally simpler compounds to facilitate analysis and improvement. Herein, we report a new [NiFe]‐based catalyst for O2 reduction via an O2 adduct. Structural investigations reveal the first example of a side‐on iron(IV) peroxo complex. Abstract : Dioxygen‐tolerant [NiFe] hydrogenases catalyze not only the conversion of H2 into 2 H + and 2 e − but also the reduction of O2 to H2 O. A new [NiFe]‐based complex is a synthetic mimic of such hydrogenases and catalyzes O2 reduction via an O2 adduct, which was shown to be the first example of a side‐on iron(IV) peroxo complex.